Common variation in atrial fibrillation: navigating the path from genetic association to mechanism. (4th January 2016) - Tucker, Nathan R.; Clauss, Sebastian; Ellinor, Patrick T.
Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia with well-established clinical and genetic risk components. Genome-wide association studies (GWAS) have identified 17 independent susceptibility signals for AF at 14 genomic regions, but the mechanisms through which these loci confer risk to AF remain largely undefined. This problem is not unique to AF, as the field of functional genomics, which attempts to bridge this gap from genotype to phenotype, has only uncovered the mechanisms for a handful of GWAS loci. Recent functional genomic studies have made great strides towards translating genetic discoveries to an underlying mechanism, but the large-scale application of these techniques to AF has remain limited. These advances, as well as the continued unresolved challenges for both common variation in AF and the functional genomics field in general, will be the subject of the following review.